Knowledge, attitudes, behaviors, and serological status related to Chagas disease among Latin American migrants in Germany: A cross-sectional study in six German cities - Wirth, Margit; Gálvez, Rosa Isela; Jochum, Johannes; Strauss, Ricardo; Kristensen, Kaja; Stich, August; Stegemann, Miriam; Stahl, Philipp; Puchner, Karl Philipp; Strasen, Jörn; Parisi, Sandra; Braasch, Trixi; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Background Little is known about knowledge, attitudes and behaviors concerning Chagas disease (CD) among Latin American migrants in Germany to inform public health decision making. Methods A cross-sectional, questionnaire-based study was conducted between March 2014 and October 2019 among Latin American migrants in six cities in Germany to obtain information on migration history, socioeconomic and insurance status, knowledge about CD, potential risk factors for Trypanosoma cruzi infection, and willingness to donate blood or organs. Results 168 participants completed the questionnaire. The four countries with the highest proportion of participants contributing to the study population were Colombia, Mexico, Peru and Ecuador. Before migrating to Europe, the majority of the study population resided in an urban setting in houses made of stone or concrete, had higher academic education and was integrated into the German healthcare and healthcare insurance system. The majority of all study participants were also willing to donate blood and organs and a quarter of them had donated blood previously. However, many participants lacked basic knowledge about symptoms and modes of transmission of Chagas disease. One out of 56 serologic tests (1.8%) performed was positive. The seropositive female participant born in Argentina had a negative PCR test and no signs of cardiac or other organ involvement. Conclusions The study population does not reflect the population structure at risk for T. cruzi infection in endemic countries. Most participants had a low risk profile for infection with T. cruzi. Although the sample size was small and sampling was not representative of all persons at risk in Germany, the seroprevalence found was similar to studies previously conducted in Europe. As no systematic screening for T. cruzi in Latin American blood and organ donors as well as in women of child-bearing age of Latin American origin is implemented in Germany, a risk of occasional transmission of T. cruzi remains.